2022
DOI: 10.1128/spectrum.02270-22
|View full text |Cite
|
Sign up to set email alerts
|

Validating Methods To Eradicate Plant-Pathogenic Ralstonia Strains Reveals that Growth In Planta Increases Bacterial Stress Tolerance

Abstract: Bacteria in the Ralstonia solanacearum species complex (RSSC) are globally distributed and cause destructive vascular wilt diseases of many high-value crops. These aggressive pathogens spread in diseased plant material and via contaminated soil, tools, and irrigation water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…UV-A radiation has been studied to a greater extent in biomedical fields because it has been observed to possess germicidal properties, which are attributed to the inhibitory effect it has on microorganisms resistant to physical sterilization methods, such as Enterococcus faecalis, Bacillus atrophaeus endospores and lentivirus [38]. However, it also has great potential for use in the control of pathogenic microorganisms of horticultural crops, since the mechanisms of action are essentially the same [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV-A radiation has been studied to a greater extent in biomedical fields because it has been observed to possess germicidal properties, which are attributed to the inhibitory effect it has on microorganisms resistant to physical sterilization methods, such as Enterococcus faecalis, Bacillus atrophaeus endospores and lentivirus [38]. However, it also has great potential for use in the control of pathogenic microorganisms of horticultural crops, since the mechanisms of action are essentially the same [44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they tested the severity of the fungus on bean (Phaseolus vulgaris) leaves by inoculating them with mycelium discs and conidial suspension, and reported a reduced radial growth rate and a delay in the onset of conidial growth [35]. Hayes et al [44] evaluated in vitro the effect of UV-C on Rasoltonia solanacearumse and observed a decrease in surviving bacterial colony-forming units (CFU) to below the detection limit after 5 min of exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic lineage, known historically and for regulatory purposes as Race 3 biovar 2, is a U.S. Select Agent pathogen because it threatens American potato production (Hayes et al, 2022;Lambert, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic lineage, known historically and for regulatory purposes as Race 3 biovar 2, is a U.S. Select Agent pathogen because it threatens American potato production (Hayes et al., 2022 ; Lambert, 2002 ). Understanding the mechanism of host resistance will be key to developing effective disease resistance to mitigate this threat (Kim et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%